Application of simultaneous thermoelectric cooling and heating to improve the performance of a solar still: An experimental study and exergy analysis. (1st April 2020) - Shoeibi, Shahin; Rahbar, Nader; Abedini Esfahlani, Ahad; Kargarsharifabad, Hadi
Highlights: Using simultaneous heating and cooling of thermoelectric modules was studied. This modification increases the temperature difference between water and glass. This improvement increases the water productivity by 2.32 times. This improvement increases the solar still's efficiency by 1.76 times. Water price in the modified solar still is 60% lower than the conventional ones. Abstract: The performance of solar stills is affected by various parameters (e.g. solar radiation, water depth, thermal insulation, and the temperature difference between glass and water). There are two alternatives to increase the temperature difference between glass and water: increasing the water or reducing the glass temperatures. The present study aims to investigate the effect of simultaneous thermoelectric cooling and heating on the performance of a solar still. The experiments were conducted during 8 days in Tehran, Iran (35°41′N, 51°19′E). The setup consisted of a double-slope solar still and a thermoelectric enhancing system that was used to cool the glass cover and heat the water, simultaneously. The cold side of the thermoelectric modules cools a water stream which passes on the glass cover. On the other side (hot side) of the thermoelectric modules, there flows another water stream passing through a helical coil heat exchanger which is located inside the solar still in the water. The obtained results, compared to the passive solar still, indicated that this modification improves the productivity by 2.32 times and generates 76.4% of the efficiency. Moreover, it is observed that the maximum exergy efficiency in the conventional and modified solar stills is about 1.48% and 0.8%, respectively. Also, the economic analysis showed that the price of the produced water for active and passive solar stills were about 0.105 and 0.176 $/L/m 2 respectively.